Spin-crossover materials properties and applications - Halcrow, Malcolm A. (Chichester : J. Wiley and Sons, Inc., 2013)
"The phenomenon of spin-crossover has a large impact on the physical properties of a solid material, including its colour, magnetic moment, and electrical resistance. Some materials also show a structural phase change during the transition. Several practical applications of spin-crossover materials have been demonstrated including display and memory devices, electrical and electroluminescent devices, and MRI contrast agents. Switchable liquid crystals, nanoparticles, and thin films of spin-crossover materials have also been achieved.Spin-Crossover Materials: Properties and Applications presents a comprehensivesurvey of recent developments in spin-crossover research, highlighting the multidisciplinary nature of this rapidly expanding field. Following an introductory chapter which describes the spin-crossover phenomenon and historical development of the field, the book goes on to cover a wide range of topics including Spin-crossover in mononuclear, polynuclear and polymeric complexes Structure: function relationships in molecular spin-crossover materials Charge-transfer-induced spin-transitions Reversible spin-pairing in crystalline organic radicals Spin-state switching in solution Spin-crossover compounds in multifunctional switchable materials and nanotechnology Physical and theoretical methods for studying spin-crossover materials Spin-Crossover Materials: Properties and Applications is a valuable resource for academic researchers working in the field of spin-crossover materials and topics related to crystal engineering, solid state chemistry and physics, and molecular materials. Postgraduate students will also find this book useful as a comprehensive introduction to the field"--
Machine generated contents note: List of Contributors xv Preface xvii 1 The Development of Spin-Crossover Research 1 Keith S. Murray 1.1 Introduction 1 1.2 Discrete Clusters of SCO Compounds 4 1.3 1D Chains of FeII SCO Materials 22 1.4 1D Chains of FeIII SCO Materials 28 1.5 2D Sheets of FeII SCO Materials 29 1.6 3D Porous SCO Materials 30 1.7 Some Recent Developments in Mononuclear SCO FeII, FeIII and CoII Compounds 33 1.8 Multifunctional/Hybrid SCO Materials 37 1.9 Developments in Instrumental Methods in Spin-Crossover Measurements 40 1.10 Applications of Molecular Spin-Crossover Compounds 41 1.11 Summary 42 2 Novel Mononuclear Spin-Crossover Complexes 55 Birgit Weber 2.1 Introduction and General Considerations 55 2.2 Novel Coordination Numbers (CN), Coordination Geometries and Metal Centres 57 2.3 Iron Complexes with Novel Ligand Donor Atoms and New Ligand Systems 65 2.4 Other Examples 70 2.5 Conclusion and Outlook 72 3 Spin-Crossover in Discrete Polynuclear Complexes 77 Juan Olguin and Sally Brooker 3.1 Introduction 77 3.2 Dinuclear Iron(II) Complexes 79 3.3 Higher Nuclearity Iron(II) Compounds 98 3.4 Iron(III) 104 3.5 Cobalt(II) 109 3.6 Dinuclear Chromium(II) Complex 111 3.7 Concluding Remarks 112 4 Polymeric Spin-Crossover Materials 121 M. Carmen Munoz and Jose Antonio Real 4.1 Introduction 121 4.2 One-Dimensional SCO-CPs 121 4.3 Two-d = Dimensional SCO-CPs 128 4.4 Three-Dimensional SCO-CPs 133 4.5 Conclusion 138 5 Structure:Function Relationships in Molecular Spin-Crossover Materials 147 Malcolm A. Halcrow 5.1 Introduction 147 5.2 Molecular Shape 150 5.3 Crystal Packing 155 5.4 Cooperativity Mediated by Disorder 158 5.5 Compounds Showing Wide Thermal Hysteresis 158 5.6 Other Noteworthy Compounds 162 5.7 Conclusions 164 6 Charge Transfer-Induced Spin-Transitions in Cyanometallate Materials 171 Kim R. Dunbar, Catalina Achim and Michael Shatruk 6.1 Introduction 171 6.2 Characterization of CTIST Compounds 173 6.3 CTIST in Coordination Polymers 174 6.4 CTIST in Nanoscale Materials 189 6.5 CTIST in Polynuclear Transition Metal Complexes 195 6.6 Summary and Outlook 198 7 Valence Tautomeric Transitions in Cobalt-dioxolene Complexes 203 Colette Boskovic 7.1 Introduction 203 7.2 Induction of Valence Tautomeric Transitions 205 7.3 Other Factors that Contribute to the Valence Tautomeric Transition 210 7.4 Polynuclear Valence Tautomeric Complexes 214 7.5 Bifunctional Valence Tautomeric Complexes 218 7.6 Concluding Remarks 220 8 Reversible Spin Pairing in Crystalline Organic Radicals 225 Jeremy M. Rawson and John J. Hayward 8.1 Introduction 225 8.2 Radical Pairs: Solution and Gas Phase Studies 226 8.3 Dimerisation in the Solid State 229 8.4 Summary and Future Perspectives 234 9 Breathing Crystals from Copper Nitroxyl Complexes 239 Victor Ovcharenko and Elena Bagryanskaya 9.1 Introduction 239 9.2 Structural and Magnetic Anomalies 241 9.3 Relationship Between the Chemical Step and the Physical Property 245 9.4 Relationship Between the Thermally Induced Reorientation of Aromatic Solvate Molecules and the Character of the Magnetic Anomaly 251 9.5 EPR Study of Breathing Crystals 255 9.6 Classification of Spin-Transitions in Breathing Crystals and Correlations with Magnetic Susceptibility 261 9.7 The Detailed Magnetic Structure of Breathing Crystals 266 9.8 EPR-detected LIESST on Breathing Crystals 272 9.9 Conclusion 275 10 Spin-State Switching in Solution 281 Matthew P. Shores, Christina M. Klug and Stephanie R. Fiedler 10.1 Introduction and Scope 281 10.2 Spin-Crossover: Solid State Versus Solution 282 10.3 Practical Considerations 283 10.4 Spin-Crossover in Solution 285 10.5 Ligation Changes Driving Spin-State Switching in Solution 288 10.6 Second Coordination Sphere Triggers for Spin-State Switching 291 10.7 Challenges and Opportunities 294 10.8 Conclusions/Outlook 295 11 Multifunctional Materials Combining Spin-Crossover with Conductivity and Magnetic Ordering 303 Osamu Sato, Zhao-Yang Li, Zi-Shuo Yao, Soonchul Kang and Shinji Kanegawa 11.1 Introduction 303 11.2 Spin-Crossover and Conductivity: Spin-Crossover Conductors 303 11.3 Spin-Crossover and Magnetic Interaction: Spin-Crossover Magnets 308 12 Amphiphilic and Liquid Crystalline Spin-Crossover Complexes 321 Shinya Hayami 12.1 Introduction 321 12.2 Unique Magnetic Properties of SCO Cobalt(II) Compounds with Long Alkyl Chains 322 12.3 Liquid Crystalline SCO Compounds 325 12.4 Langmuir-Blodgett Films and Amphiphilic SCO Compounds 331 12.5 Conclusion and Outlook 339 13 Luminescent Spin-Crossover Materials 347 Helena J. Shepherd, Carlos M. Quintero, G℗ábor Molnar, Lionel Salmon and Azzedine Bousseksou 13.1 General Introduction 347 13.2 Introduction to Luminescent Materials and Luminescence Energy Transfer 348 13.3 Electronic Transitions and Optical Properties of Spin-Crossover Complexes 358 13.4 Materials with Combined Spin-Crossover and Luminescent Functionalities 361 13.5 Concluding Remarks 371 14 Nanoparticles, Thin Films and Surface Patterns from Spin-Crossover Materials and Electrical Spin State Control 375 Paulo Nuno Martinho, Cyril Rajnak and Mario Ruben 14.1 Introduction 375 14.2 Nanoparticles and Nanocrystals 376 14.3 Thin Films 387 14.4 Surface Patterns 393 14.5 Electrical Spin State Control 396 14.6 Conclusion 399 15 Ultrafast Studies of the Light-Induced Spin Change in Fe(II)-Polypyridine Complexes 405 Majed Chergui 15.1 Introduction 405 15.2 Properties of Fe(II) Complexes 406 15.3 From the Singlet to the Quintet State 408 15.4 Ultrafast X-Ray Studies 415 15.5 Summary and Outlook 417 16 Real-Time Observation of Spin-Transitions by Optical Microscopy 425 Francois Varret, Ahmed Slimani, Damien Garrot, Yann Garcia and Anil D. Naik 16.1 Introduction 425 16.2 Experimental Aspects 426 16.3 Selected Investigations 429 16.4 Conclusions and Prospects 439 17 Theoretical Prediction of Spin-Crossover at the Molecular Level 443 Robert J. Deeth, Christopher M. Handley and Benjamin J. Houghton 17.1 Introduction 443 17.2 Beginnings: Valence Bond and Ligand Field Theories 443 17.3 Quantum Chemistry 446 17.4 Empirical Methods 449 17.5 Conclusions 452 18 Theoretical Descriptions of Spin-Transitions in Bulk Lattices 455 Cristian, Enachescu, Masamichi Nishino and Seiji Miyashita 18.1 Introduction 455 18.2 Elastic Interaction Models for Spin-Crossover Systems 457 18.3 Mechano-Elastic Model 463 18.4 Conclusions 471 19 Optimizing the Stability of Trapped Metastable Spin States 475 Jean-Francois Letard, Guillaume Chastanet, Philippe Guionneau and Cedric Desplanches 19.1 Introduction 475 19.2 Light-Induced Excited Spin-State Trapping (LIESST) Effect 476 19.3 The T(LIESST) Approach: The Case of Mononuclear Compounds 479 19.4 The T(LIESST) Approach: An Extension to Polynuclear Iron(II) Complexes 487 19.5 Simulation and Extrapolation of a T(LIESST) Experiment 495 19.6 Conclusions 500 20 Piezo- and Photo-Crystallography Applied to Spin-Crossover Materials 507 Philippe Guionneau and Eric Collet 20.1 Introduction 507 20.2 Spin-Crossover and Piezo-Crystallography 507 20.3 Crystallography of Photoexcited SCO Materials 512 21 Spin-Transitions in Metal Oxides 527 Jean-Pascal RUEFF 21.1 Introduction 527 21.2 RIXS: A Probe of the 3d Electronic Properties 530 21.3 Experimental Results 533 21.4 Conclusions and Perspectives 538 References 540 Index.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Spintronics -- Materials; Nanostructured materials -- Electric properties; Nanostructured materials -- Magnetic properties; Electron paramagnetic resonance; Electronic books